The Impact of Marketing Mix, Consumer’s Characteristics, and Psychological Factors to Consumer’s Purchase Intention on Brand “W” in Surabaya - Aristia Rosiani Nugroho; Angela Irena (iBuss Management, 2017)
This research is conducted to find out the impact of marketing mix, customer’s characteristics, and psychological factors toward consumers’ purchase intention in cosmetic industry. The object of this research is Brand “W”, the biggest player in Halal cosmetic market in Asia Pacific. This research will focus on marketing activities conducted by Brand “W” to arouse consumers’ purchase intention. However, unlike other researches, this research will not only use marketing theory, but also consumer behavior theory to complement and strengthen the research’s accuracy. From marketing theory, marketing mix are used with the attributes of product, price, promotion, and place. From consumer behavior theory, consumer’s characteristics (i.e. cultural, social, and personal influences) and psychological influences are used.Multiple regression analysis is used to analyze the response from 138 respondents. The sampling method used is probability sampling, especially simple random sampling. From the analysis, marketing mix, consumer’s characteristics, and psychological factors have simultaneous significant impact toward consumer’s purchase intention on Brand “W”. However, partially, only product, culture influences, and psychological influences have significant impact toward consumer’s purchase intention on Brand “W”. Keywords: cosmetics, marketing mix, consumer behavior, purchase intention